THE ROLE OF MUSEUMS’ SUSTAINABILITY IN CULTURAL TOURISM AND VISITORS’ PATRONAGE IN RIVERS STATE OF NIGERIA (American Journal of Research in Humanities and Social Sciences, 2022)
Concerns have been expressed regarding Nigeria’s low tourism performance and the role of museums in cultural sustainability in driving sustainable tourism in the nation against the backdrop of government’s claim of efforts at repositioning the museums for effective service delivery. Therefore, this empirical study evaluated museums’ sustainable practices and visitors’ patronage in Rivers State of Nigeria. The survey research design was adopted and data was collected from both primary and secondary sources. A structured questionnaire was designed for collection of primary data from a sample of 138 visitors drawn from the purposive sampling technique. Univariate analysis was done using simple percentage, mean score and standard deviation while bivariate analysis was performed using the Pearson Product Moment correlation technique to determine the strength of relationship the independent and dependent variables of the study. The study found that a positive and significant relationship exists between collection, conservation, exhibition and enlightenment about the artefacts and frequency of visits to the Museums in Port Harcourt. Drawing from the findings, the study recommended that the government should also introduce digital exhibition, embark on more public enlightenment programmes, collect more artefacts from other Nigerian cultures and train tour guides on communications skills.